Building Organizational Resilience in the Era of Uncertainty: Strategies and Best Practices - Khuan, Hendri (Penelitian dan Pengembangan Ilmu, 2024)
This literature review aims to explore strategies and best practices for building organizational resilience in the era of uncertainty. The research synthesizes existing literature to identify key predictors of organizational resilience, including resilient leadership, human capital management strategies, proactive resilience approaches, and cost optimization techniques. The methodology employed in this study involves a systematic literature review using reputable international academic databases over the past five years. Findings reveal that resilient leadership plays a crucial role in fostering organizational resilience by cultivating a resilient culture, enhancing awareness, facilitating learning processes, and strengthening physiological capital. Additionally, human capital management strategies focusing on individual capability development and resilience-building contribute significantly to organizational resilience. Proactive resilience approaches and cost optimization techniques further enhance organizational resilience by enabling quick adaptation and response to unexpected events. This study highlights the importance of adopting a multi-level approach to cost optimization and emphasizes the need for empirical research to validate the effectiveness of different resilience-building strategies. The findings offer practical insights for organizations seeking to enhance their resilience in uncertain environments.